2011
DOI: 10.1100/tsw.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Epithelial Cancer Stem Cells

Abstract: The last decade witnessed an explosion of interest in cancer stem cells (CSCs). The realization of epithelial ovarian cancer (EOC) as a CSC-related disease has the potential to change approaches in the treatment of this devastating disease dramatically. The etiology and early events in the progression of these carcinomas are among the least understood of all major human malignancies. Compared to the CSCs of other cancer types, the identification and study of EOC stem cells (EOCSCs) is rather difficult due to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 255 publications
(308 reference statements)
0
15
0
Order By: Relevance
“…The stem cell markers that were evaluated in this study are ALDH1 [13], CD24 [13], CD44 [14], CD133 [15], NOTCH3 [4], SOX2 [13], and CD117 [14]. All of these stem cell markers, except CD117, were more highly expressed in the SFCs than in the primary cancer cells (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The stem cell markers that were evaluated in this study are ALDH1 [13], CD24 [13], CD44 [14], CD133 [15], NOTCH3 [4], SOX2 [13], and CD117 [14]. All of these stem cell markers, except CD117, were more highly expressed in the SFCs than in the primary cancer cells (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…CSCs have three main properties: (i) they express distinct surface markers; (ii) they are selectively endowed with tumorigenic capacity; and (iii) they sustain the growth of heterogeneous cancer tissues, therefore, displaying two of the functional hallmarks of stem cells, namely self-renewal and differentiation into multiple cell types [4][5][6][7]. CSCs also contribute to cancer recurrence through their resistance to anticancer drugs and their tumorigenic capacity, and many previous studies show that CSCs can resist chemoradiation therapy [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer represents a heterogeneous group of distinct tumors exhibiting a wide range of morphological characteristics, clinical manifestations, genetic alterations and tumors behaviours (Conic et al, 2011). Goff (2012), reviewed that ovarian cancer had always been called ''The silent killer'' because symptoms are not thought to develop until advanced stages, when chances of cure were very poor.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of stem cell markers, response to therapy, and best system for in vivo analysis needs to be conducted between different methods for generating/selection of CSCs. It has been suggested that there are different types of CSCs with different expression patterns of stem cell markers and different prognosis for patients [10][11][12] , thus further definition of what type of CSCs are generated by this protocol may help determine how they relate to human malignancy. Finally, in order to rigorously demonstrate that the CSCs isolated from this protocol are definitive CSCs, cells need to be injected into immunocompromised mice in a limiting dilution assay.…”
Section: Discussionmentioning
confidence: 99%